Theory of justice for contemporary Ecuadorian constitutionalism (2014)
Ecuador, with a constituent process embodied in a Constituent National Assembly, with the announcement of the issuance of a new Constitution submitted to a referendum the people of Ecuador, aiming thus to overcome a decade of successive political crises of conflict between executive-legislative branches.   From this context, the author places the reader in the scenario of justice, concepts and relationships, this is how the question arises which starts the text: What is Justice? If this is the path that leads to happiness, what is happiness? , if for Kelsen “Justice is social happiness guaranteed by a social order”, at the same it leads then him to ask himself, what is a fair social order? And it is precisely the construction of a fair social order, which takes the development of this work. Advancing in the design of a fair social order or fair institutions, the development of this text includes approaches from Plato to great exponents of contemporary social philosophy, as John Rawls and Jürgen Habermas.